2016
DOI: 10.1080/00221325.2016.1218322
|View full text |Cite
|
Sign up to set email alerts
|

Family Environments and Children's Executive Function: The Mediating Role of Children's Affective State and Stress

Abstract: There is increasing evidence that inadequate family environments (family material environment and family psychosocial environment) are not only social problems but also factors contributing to adverse neurocognitive outcomes. In the present study, the authors investigated the relationship among family environments, children's naturalistic affective state, self-reported stress, and executive functions in a sample of 157 Chinese families. These findings revealed that in inadequate family material environments, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Our finding of a positive association between positive affect and shifting was also reported by Cserj esi et al 2009who found a positive relationship between positive affect and faster reaction times on the Trails Making Test A and B. He and Yin (2016) also reported a positive relationship between negative affect and shifting performance, but, in contrast to our findings, He and Yin (2016) reported no effects between measures of planning, inhibition and updating with negative affect and no relationship between positive affect and any EF measure. It is likely that these differences across studies could be explained by variation in sampling which might have affected EF (e.g., age; Miyake et al, 2000).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our finding of a positive association between positive affect and shifting was also reported by Cserj esi et al 2009who found a positive relationship between positive affect and faster reaction times on the Trails Making Test A and B. He and Yin (2016) also reported a positive relationship between negative affect and shifting performance, but, in contrast to our findings, He and Yin (2016) reported no effects between measures of planning, inhibition and updating with negative affect and no relationship between positive affect and any EF measure. It is likely that these differences across studies could be explained by variation in sampling which might have affected EF (e.g., age; Miyake et al, 2000).…”
Section: Discussionsupporting
confidence: 85%
“…It is likely that these differences across studies could be explained by variation in sampling which might have affected EF (e.g., age; Miyake et al, 2000). Our participants were healthy volunteers aged 18-25 years, whereas Simpson et al (2014) recruited elderly participants, Cserj esi et al (2009) recruited females with an obesity diagnosis, and He and Yin (2016) recruited families with children.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, mediation models help us to better understand the interaction between macro-environmental and the development of EF: the links between SES and EF are at least partially explained by associated variations in parenting behaviors (57). Besides, the level of stress, associated with a negative affectivity, has also been pointed out for its mediation role between macro-environmental factors and the development of EF (58). …”
Section: The Possible Role Of Ecological Factors On the Development Omentioning
confidence: 99%